Investigating the association between cancer and the risk of dementia: Results from the Memento cohort. Issue 9 (3rd March 2021) - Chamberlain, Jonviea D.; Rouanet, Anaïs; Dubois, Bruno; Pasquier, Florence; Hanon, Olivier; Gabelle, Audrey; Ceccaldi, Mathieu; Krolak‐Salmon, Pierre; Béjot, Yannick; Godefroy, Olivier; Wallon, David; Gentric, Armelle; et al.
Abstract: Introduction: Studies on the association of cancer and risk of dementia are inconclusive due to result heterogeneity and concerns of survivor bias and unmeasured confounding. Methods: This study uses data from the Memento cohort, a French multicenter cohort following persons with either mild or isolated cognitive complaints for a median of 5 years. Illness‐death models (IDMs) were used to estimate transition‐specific hazard ratios (HRs) and 95% confidence intervals (CIs) for incident cancer in relation to dementia from time since study entry. Results: The analytical sample (N = 2258) excluded 65 individuals without follow‐up information. At the end of follow‐up, 286 individuals were diagnosed with dementia, 166 with incident cancer, and 95 died. Incident cancer was associated with a reduced risk of dementia (HR = 0.58, 95% CI = 0.35‐0.97), with a corresponding E‐value of 2.84 (lower CI = 1.21). Discussion: This study supports a protective relationship between incident cancer and dementia, encouraging further investigations to understand potential underlying mechanisms.